Novel two-dimensional ternary compound with single-sided passivation structure and preparation method thereof

CN122977324APending Publication Date: 2026-10-27INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510520302.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

近年来,随着对该材料家族的深入研究,一些该材料家族的衍生物相继被预测,例如不同于原始的双面钝化结构,单个A-Z双原子层钝化Z-M-Z层也可产生稳定的结构,且其结构由于具有天然的垂直方向上的不对称性,该类单面钝化的材料表现出面外压电,体光伏等优异物性,但目前该类材料尚缺乏有效的制备手段

Benefits of technology

1. 本发明提出了一类新型具有单面钝化结构的新型二维三元化合物,其分子式为(MnZn+1)AZ,其中M为金属元素,A为第四主族元素,Z为第五主族元素,化合物可看作由第四主族和第五主族元素A-Z双原子层对二维MnZn+1三元化合物单面钝化所得。根据成分不同表现出不同的电学、光学和力学等性质,可以是不同带隙的半导体或磁性半金属。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977324A_ABST
    Figure CN122977324A_ABST
Patent Text Reader

Abstract

This invention relates to the field of novel MA2Z4 material family members and their chemical vapor deposition preparation, specifically a novel two-dimensional ternary compound (M2Z4) with a single-sided passivation structure. n Z n+1 This invention relates to a method for preparing AZ materials and their large-size domains and thin films. Using an Au / M metal bimetallic substrate, by reducing the supply of A to create an A-depleted environment, large-size, thickness-controllable two-dimensional ternary compounds (M...) are grown at temperatures above the melting point of Au. n Z n+1 )AZ, and then the Au substrate is etched to transfer it onto any substrate. This invention features a simple fabrication process, easy control of material composition, thickness, and size, and the ability to prepare large-area, high-quality continuous thin films, making it suitable for two-dimensional ternary compounds (M n Z n+1 AZ has laid the foundation for research and application in fields such as electronic devices, optoelectronic devices, catalysis, and energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of novel two-dimensional MA2Z4 material family members and their chemical vapor deposition preparation, specifically a novel two-dimensional (M2Z4) material family with a single-sided passivation structure. n Z n+1 AZ ternary compounds and their preparation methods, applicable to the preparation of large-size (M) ternary compounds. n Z n+1 AZ domains and thin films. Background Technology

[0002] Since scientists at the University of Manchester in the UK first obtained graphene materials with single-atom-layer and a few-atom-layer thicknesses using mechanical exfoliation in 2004, two-dimensional layered materials, represented by graphene, have attracted widespread attention due to their atomic-level thickness, ultra-high specific surface area, and unique physicochemical properties that differ significantly from bulk materials. However, almost all existing two-dimensional layered materials have corresponding three-dimensional bulk materials, which limits their types and properties. Therefore, designing and synthesizing novel two-dimensional layered materials that do not exist in nature will greatly expand the properties and applications of two-dimensional layered materials.

[0003] In 2020, a novel van der Waals layered material, MoSi2N4, not found in nature, was prepared using a CVD method involving silicon passivation of two-dimensional non-layered molybdenum nitride. This discovery led to the creation of a new family of van der Waals layered materials, MA2Z4, where M represents a metallic element, including but not limited to molybdenum, tungsten, titanium, zirconium, hafnium, vanadium, niobium, tantalum, or chromium; A represents a Group 4 element, including but not limited to silicon or germanium; and Z represents a Group 5 element, including but not limited to nitrogen, phosphorus, or arsenic. Each layer of this material consists of seven atomic layers: ZAZMZAZ, which can be viewed as passivation of ZMZ by two AZ bilayers. In recent years, with in-depth research on this material family, some derivatives of this material family have been predicted. For example, unlike the original double-sided passivation structure, a single AZ double-atom layer passivated ZMZ layer can also produce a stable structure. Moreover, due to the natural vertical asymmetry of its structure, this type of single-sided passivated material exhibits excellent physical properties such as out-of-plane piezoelectricity and bulk photovoltaics. However, there is currently no effective preparation method for this type of material. Summary of the Invention

[0004] The purpose of this invention is to provide a novel type of large-size two-dimensional (M) structure with single-sided passivation. n Z n+1 ) An AZ ternary compound and its preparation method, wherein the two-dimensional ternary compound can be regarded as an AZ bilayer paired with a two-dimensional M n Z n+1The compound is obtained by single-sided passivation. Its preparation process is simple, and the composition, thickness and size of the product are easy to control, which lays the foundation for expanding the types, properties and applications of two-dimensional MA2Z4 materials.

[0005] The technical solution of this invention is: A new class of two-dimensional ternary compounds with a single-sided passivation structure, the molecular formula of which is (M n Z n+1 )AZ, where: M is a metallic element, including but not limited to molybdenum, tungsten, titanium, zirconium, hafnium, vanadium, niobium, tantalum, or chromium; A is a Group IV element, including but not limited to silicon or germanium; Z is a Group V element, including but not limited to nitrogen, phosphorus, or arsenic; this two-dimensional ternary compound can be regarded as an AZ bilayer paired with a two-dimensional M n Z n+1 The compound is obtained by passivating one side, for example (M3Z4)AZ is ZMZMZMZAZ.

[0006] The method for preparing a novel two-dimensional ternary compound with a large-size, single-sided passivation structure employs a bimetallic layer consisting of an upper Au layer and a lower metal M layer as the growth substrate. Au serves as the diffusion channel for metal M, providing the M element. A and Z elements are introduced under a carrier gas atmosphere, and an A-depleted environment is created by reducing the supply of A element. Large-size, uniformly thick (M) compounds are catalytically grown on the Au surface using chemical vapor deposition at a reaction temperature above the melting point of Au. n Z n+1 )AZ crystal domains and their thin films, followed by etching away Au (M n Z n+1 AZ can be transferred to any matrix.

[0007] The method for preparing a novel two-dimensional ternary compound with a large-size single-sided passivation structure, wherein the bimetallic layer growth substrate is a stacked Au foil and a metal M foil; or the M element can be obtained by a coating method of magnetron sputtering or thermal evaporation on a partially high-melting-point metal foil.

[0008] The method for preparing a novel two-dimensional ternary compound with a large-size single-sided passivation structure involves introducing A and Z elements by using a precursor containing A and Z. The precursor is a solid, powder, liquid, or gas that volatilizes or decomposes to release A or Z at high temperature.

[0009] The method for preparing a novel two-dimensional ternary compound with a large-size single-sided passivation structure, wherein M is a metallic element, including molybdenum, tungsten, titanium, zirconium, hafnium, vanadium, niobium, tantalum, or chromium; A is a Group IV element, including but not limited to silicon or germanium, wherein silicon precursors include but are not limited to silicon wafers, quartz wafers, silanes, silicon powder, mixtures of silicon powder and alumina powder, quartz powder, and mixtures of quartz powder and alumina powder; germanium precursors include but are not limited to germanium wafers, germanane, germanium powder, mixtures of germanium powder and alumina powder, germanium oxide powder, and mixtures of germanium oxide powder and alumina powder; Z is a Group V element, including but not limited to nitrogen, phosphorus, or arsenic, wherein nitrogen precursors include but are not limited to ammonia, phosphorus precursors include but are not limited to white phosphorus or red phosphorus, and arsenic precursors include but are not limited to elemental arsenic.

[0010] The method for preparing a novel two-dimensional ternary compound with a large-size single-sided passivation structure, wherein the carrier gas in the chemical vapor deposition reaction is hydrogen or a mixture of hydrogen and an inert gas.

[0011] The method for preparing a novel type of large-size two-dimensional ternary compound with a single-sided passivation structure, wherein two-dimensional layered (M) structures are grown by chemical vapor deposition. n Z n+1 The temperature range for the AZ two-dimensional ternary compound is 1070℃~1200℃, and the growth time is 30 minutes~300 minutes. By extending the growth time, the (M) can be increased. n Z n+1 The size of the AZ domains is determined to obtain a complete continuous thin film.

[0012] The method for preparing a novel two-dimensional ternary compound with a single-sided passivation structure, the novel (M n Z n+1 The single-sided passivation structure of AZ two-dimensional ternary compounds can be achieved by reducing the supply of element A to create an A-depleted environment, including: increasing the distance between the A element precursor and the growth substrate, reducing the amount of A element precursor, reducing the growth temperature, or any combination of two or three operations.

[0013] The method for preparing a novel type of large-size two-dimensional ternary compound with a single-sided passivation structure, the novel (M n Z n+1 The thickness of AZ 2D ternary compounds can be controlled by altering the amount of Z element precursor, growth temperature, and growth time during chemical vapor deposition: increasing the growth temperature, extending the growth time, or increasing the amount of Z element precursor can yield thicker (M) ternary compounds. n Z n+1 )AZ two-dimensional ternary compound.

[0014] The method for preparing a novel type of large-size two-dimensional ternary compound with a single-sided passivation structure, as described above, involves the transfer (M... n Z n+1 When processing AZ two-dimensional ternary compounds, a layer of polymer is first uniformly coated on its surface to prevent damage during subsequent processing. Then, the Au substrate is removed by etching with an Au etching solution to obtain the polymer / (M n Z n+1 The AZ two-dimensional ternary compound was used, and finally the composite film was placed on the target substrate. The polymer protective film was dissolved and removed using an organic solvent.

[0015] The method for preparing a novel two-dimensional ternary compound with a large-size single-sided passivation structure uses a polymer that is one or a mixture of two or more of polymethyl methacrylate, polyethylene, polystyrene, and polypropylene. The etching solution for Au is a commercial gold etchant. The organic solvent used to remove the polymer protective layer is one or a mixture of two or more of ketones, chlorinated hydrocarbons, halogenated hydrocarbons, and aromatic hydrocarbons.

[0016] The design concept of this invention is: Structurally, this type of novel two-dimensional ternary compound (M) with a single-sided passivation structure n Z n+1 AZ materials can be viewed as a two-dimensional M-type material consisting of a double layer of AZ atoms from Group 4 and Group 5 elements. n Z n+1 The result is obtained by single-sided passivation of a ternary compound.

[0017] This invention employs an Au / M bimetallic substrate, using Au as a diffusion channel for metal M to provide M element, ensuring a sufficient supply of M element; by reducing the supply of A element, an A-depleted environment is created, ensuring an extreme lack of A element in the growth matrix, thus achieving M… n Z n+1 A single-sided passivated structure of the compound; chemical vapor deposition is performed at temperatures above the melting point of gold, utilizing the high catalytic activity of the liquid Au growth substrate and the rapid diffusion of precursor materials on the liquid gold surface to achieve large-size (M... n Z n+1 Preparation of AZ materials.

[0018] The advantages and beneficial effects of this invention are: 1. This invention proposes a novel class of two-dimensional ternary compounds with a single-sided passivation structure, the molecular formula of which is (M n Z n+1 )AZ, where M is a metallic element, A is a Group 4 element, and Z is a Group 5 element. The compound can be viewed as a two-dimensional structure consisting of a double layer of Group 4 and Group 5 elements AZ and M. n Z n+1It is obtained by single-sided passivation of ternary compounds. Depending on the composition, it exhibits different electrical, optical and mechanical properties, and can be a semiconductor or magnetic half-metal with different band gaps.

[0019] 2. This invention proposes a novel two-dimensional (M) structure with a large-size, single-sided passivation feature. n Z n+1 The chemical vapor deposition method for AZ ternary compounds has the advantages of simple preparation process, easy control of product composition, thickness and size, and ability to prepare large-area high-quality continuous thin films.

[0020] 3. This invention relates to a novel two-dimensional ternary compound (M n Z n+1 AZ has laid the foundation for research and application in fields such as electronic devices, optoelectronic devices, catalysis, and energy. Attached Figure Description Figure 1 To grow novel two-dimensional (M) structures with single-sided passivation using CVD method n Z n+1 Schematic diagram of the experimental setup for the AZ ternary compound; Figure 2 Scanning electron microscope (SEM) images of two-dimensional (W5N6)SiN ternary compounds obtained on Au / W substrates at different growth times. Where: a, 60 min; b, 180 min; c, 300 min; Figure 3 Figure a shows an atomic force microscope (AFM) image of the (W5N6)SiN thin film transferred onto a SiO2 / Si substrate. Figure b shows the height curve of (W5N6)SiN measured by atomic force microscopy. The horizontal axis Distance represents the measured distance (μm), and the vertical axis Height represents the measured thickness (nm). Figure 4 The secondary ion mass spectrometry image is a surface scan of the Au / W substrate with (W5N6)SiN grown on it, showing that the sample contains three elements: W, Si, and N. Figure 5 Figure a shows a high-resolution scanning transmission electron micrograph of (W5N6)SiN in a plane. Figure b shows a high-resolution integrated differential phase scanning transmission electron micrograph of a cross-section of (W5N6)SiN. Figure c shows a high-resolution scanning transmission electron micrograph of a cross-section of (W5N6)SiN. Figure d shows an atomic structure model of (W5N6)SiN along the a-axis. Figure e shows an atomic structure model of (W5N6)SiN along the c-axis. Figure 6Figure a shows the micro-area absorption spectrum of the (W5N6) SiN thin film transferred to a quartz plate. The horizontal axis represents wavelength (nm), and the vertical axis represents absorbance (au). Figure b is the Tauc plot obtained from the absorption spectrum in Figure a. The horizontal axis represents photon energy (eV), and the vertical axis represents (αhν). 2 The x-axis represents the variable (au) related to the absorption coefficient. The intersection of the extended linear segment of the curve with the x-axis represents the direct band gap value of the material. Figure c shows the photoluminescence spectrum of the (W5N6)SiN sample transferred to SiO2 / Si. The x-axis represents photon energy (eV), and the y-axis represents the variable (au) related to the luminescence intensity. Figure 7 Scanning electron microscope image of a two-dimensional (Mo5N6)SiN ternary compound grown on an Au / Mo substrate; Figure 8 A secondary ion mass spectrometry (TIMS) image of an Au / Mo substrate with (Mo5N6)SiN grown on it, showing compositional analysis. Detailed Implementation In the specific implementation process, a bimetallic layer consisting of an upper Au layer and a bottom metal M layer is used as the growth substrate. Au serves as the diffusion channel for M, providing the M element. A and Z elements are introduced under a carrier gas atmosphere. By reducing the supply of A element, an A-depleted environment is created. Using CVD technology at a reaction temperature higher than the melting point of Au, M is catalytically grown on the Au surface. n Z n+1 )AZ single crystal or thin film, subsequent etching away Au will (M n Z n+1 AZ can be transferred to any substrate or used directly with the substrate.

[0021] The bimetallic layer growth substrate uses stacked Au foil and metal M foil, which simplifies the substrate preparation process and makes the operation simple; or the M element can be obtained by magnetron sputtering or thermal evaporation on some high-melting-point metal foils, which can precisely control the thickness and uniformity of the M element and is beneficial to the controllability of the subsequent growth process.

[0022] By introducing A and Z elements through the use of precursors containing A and Z, the precursors can be solids, powders, liquids, or gases that volatilize or decompose to release A or Z at high temperatures, thereby enhancing operational flexibility.

[0023] In the chemical vapor deposition (CVD) reaction, the carrier gas is hydrogen or a mixture of hydrogen and an inert gas; CVD grows two-dimensional layered structures (M... n Z n+1The temperature range for the AZ two-dimensional ternary compound is 1070℃~1200℃, and the growth time is 30 minutes~300 minutes. By extending the growth time, the (M) can be increased. n Z n+1 The size of the AZ domains is determined to obtain a complete continuous thin film.

[0024] New type (M) n Z n+1 The single-sided passivation structure of AZ two-dimensional ternary compounds can be achieved by reducing the supply of alumina (A) to create an A-depleted environment. This can be achieved through one of the following operations: increasing the distance between the A precursor and the growth substrate, reducing the amount of A precursor, or decreasing the growth temperature; or by combining any two or three operations. Combining different methods allows for more precise control of the A supply, which is beneficial for obtaining high-quality single-sided passivation structures. New type (M) n Z n+1 The thickness of AZ two-dimensional ternary compounds can be controlled by altering the amount of Z element precursor, growth temperature, and growth time during chemical vapor deposition: extending the growth time or increasing the amount of Z element precursor can yield thicker (M) ternary compounds. n Z n+1 )AZ two-dimensional ternary compound.

[0025] In the transfer (M n Z n+1 When processing AZ two-dimensional ternary compounds, a layer of polymer is first uniformly coated on its surface to prevent damage during subsequent processing. Then, the Au substrate is removed by etching with an Au etching solution to obtain the polymer / (M n Z n+1 The AZ two-dimensional ternary compound was used, and finally the composite film was placed on the target substrate. The polymer protective film was dissolved and removed using an organic solvent.

[0026] The polymer used is one or a mixture of two or more of polymethyl methacrylate, polyethylene, polystyrene, and polypropylene. The etching solution for Au is a commercial gold etchant. The organic solvent used to remove the polymer protective layer is one or a mixture of two or more of ketones, chlorinated hydrocarbons, halogenated hydrocarbons, and aromatic hydrocarbons.

[0027] This method can effectively prepare novel two-dimensional ternary compounds with single-sided passivation structures, achieving controllable preparation of material composition, thickness, and size.

[0028] The present invention will now be described in further detail with reference to embodiments and accompanying drawings. Example 1

[0029] First, such as Figure 1As shown, in this embodiment, Au foil / W foil (Au foil 5 mm × 5 mm × 10 μm, purity 99.99 wt%, W foil 5 mm × 5 mm × 50 μm, purity 99.95 wt%) and silicon wafer (10 mm × 10 mm × 500 μm, purity 99.9999 wt%) are placed in the central area of ​​a pyrolytic boron nitride tube (inner diameter 16 mm, length 20 cm), with the silicon wafer placed upstream of the Au foil / W foil, 10 mm away from the bimetallic strip. Then, the Au foil / W foil, silicon wafer, and pyrolytic boron nitride tube are placed together in a horizontal reactor (quartz furnace tube). The central region (22 mm in diameter, 20 mm in reaction zone length) is heated to 1070 °C in a hydrogen atmosphere to melt the Au foil (hydrogen flow rate of 200 mL / min and heating rate of 30 °C / min during heating). When the furnace temperature reaches 1070 °C, it is held for 10 minutes, and then a mixture of ammonia and hydrogen is introduced (gas flow rates of 10 mL / min for ammonia and 200 mL / min for hydrogen) to begin the growth of two-dimensional tungsten silicon nitride crystals. The growth time is 60 minutes. After the growth is completed, it is rapidly cooled at a rate of 500 °C / min to obtain two-dimensional tungsten silicon nitride crystals on the surface of the Au foil.

[0030] Then, a polymethyl methacrylate (PMMA) ethyl lactate solution (PMMA accounting for 4 wt%) was dropped onto the Au surface on which two-dimensional tungsten nitride silicon crystals were grown. A PMMA film was coated by spin coating at 3000 rpm. After baking at 120°C for 10 minutes, the film was placed in a commercial gold etchant and reacted at 50°C for 120 minutes to dissolve the Au substrate, transferring the PMMA / tungsten nitride silicon crystals to the SiO2 / Si substrate. The PMMA was then dissolved with acetone at 70°C, thus achieving the successful transfer of the two-dimensional tungsten nitride silicon crystals.

[0031] The composition, crystal structure, morphology and thickness of tungsten silicon nitride crystals were characterized by secondary ion mass spectrometry, scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The results showed that the obtained tungsten silicon nitride crystals were two-dimensional (W5N6)SiN crystals with a hexagonal structure, exhibiting a triangular shape, with an average size of 20 μm and a thickness of about 1.87 nm, and high crystal quality. Example 2

[0032] First, such as Figure 1As shown, in this embodiment, Au foil / W foil (Au foil 5 mm × 5 mm × 10 μm, purity 99.99 wt%, W foil 5 mm × 5 mm × 50 μm, purity 99.95 wt%) and silicon wafer (10 mm × 10 mm × 500 μm, purity 99.9999 wt%) are placed in the central area of ​​a pyrolytic boron nitride tube (inner diameter 16 mm, length 20 cm), with the silicon wafer placed upstream of the Au foil / W foil, 10 mm away from the bimetallic strip. Then, the Au foil / W foil, silicon wafer, and pyrolytic boron nitride tube are placed together in a horizontal reactor (quartz furnace tube diameter 22 mm, reverse...). The central region (with a length of 20 mm) is heated to 1070°C in an atmosphere of hydrogen and argon to melt the Au foil (the flow rates of hydrogen and argon during heating are both 100 mL / min, and the heating rate is 30°C / min). When the furnace temperature reaches 1070°C, it is held for 10 minutes, and then a mixture of ammonia, hydrogen, and argon is introduced (the gas flow rates are 10 mL / min for ammonia and 100 mL / min for both hydrogen and argon) to begin the growth of two-dimensional tungsten silicon nitride crystals. The growth time is 60 minutes. After the growth is completed, it is rapidly cooled at a rate of 500°C / min to obtain two-dimensional tungsten silicon nitride crystals on the surface of the Au foil.

[0033] Then, a polymethyl methacrylate (PMMA) ethyl lactate solution (PMMA accounting for 4 wt%) was dropped onto the Au surface on which two-dimensional tungsten nitride silicon crystals were grown. A PMMA film was coated by spin coating at 3000 rpm. After baking at 120°C for 10 minutes, the film was placed in a commercial gold etchant and reacted at 50°C for 120 minutes to dissolve the Au substrate, transferring the PMMA / tungsten nitride silicon crystals to the SiO2 / Si substrate. The PMMA was then dissolved with acetone at 70°C, thus achieving the successful transfer of the two-dimensional tungsten nitride silicon crystals.

[0034] The composition, crystal structure, morphology and thickness of tungsten silicon nitride crystals were characterized by secondary ion mass spectrometry, scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The results showed that the obtained tungsten silicon nitride crystals were two-dimensional (W5N6)SiN crystals with a hexagonal structure, exhibiting a triangular shape, with an average size of 20 μm and a thickness of about 1.87 nm, and high crystal quality. Example 3

[0035] First, such as Figure 1As shown, in this embodiment, Au foil / W foil (Au foil 5 mm × 5 mm × 10 μm, purity 99.99 wt%, W foil 5 mm × 5 mm × 50 μm, purity 99.95 wt%) and silicon wafer (10 mm × 10 mm × 500 μm, purity 99.9999 wt%) are placed in the central area of ​​a pyrolytic boron nitride tube (inner diameter 16 mm, length 20 cm), with the silicon wafer placed upstream of the Au foil / W foil, 10 mm away from the bimetallic strip. Then, the Au foil / W foil, silicon wafer, and pyrolytic boron nitride tube are placed together in a horizontal reactor (quartz furnace tube). The central region (22 mm in diameter, 20 mm in reaction zone length) is heated to 1070 °C in a hydrogen atmosphere to melt the Au foil (hydrogen flow rate of 200 mL / min and heating rate of 30 °C / min during heating). When the furnace temperature reaches 1070 °C, it is held for 10 minutes, and then a mixture of ammonia and hydrogen is introduced (gas flow rates of 10 mL / min for ammonia and 200 mL / min for hydrogen) to begin the growth of two-dimensional tungsten silicon nitride crystals. The growth time is 180 minutes. After the growth is completed, it is rapidly cooled at a rate of 500 °C / min to obtain two-dimensional tungsten silicon nitride crystals on the surface of the Au foil.

[0036] Then, a polymethyl methacrylate (PMMA) ethyl lactate solution (PMMA accounting for 4 wt%) was dropped onto the Au surface on which two-dimensional tungsten nitride silicon crystals were grown. A PMMA film was coated by spin coating at 5000 rpm. After baking at 120°C for 10 minutes, the substrate was placed in a commercial gold etchant and reacted at 50°C for 120 minutes to dissolve the Au substrate, transferring the PMMA / tungsten nitride silicon crystals to the SiO2 / Si substrate. The PMMA was then dissolved with acetone at 70°C, thus achieving the successful transfer of the two-dimensional tungsten nitride silicon crystals.

[0037] The composition, crystal structure, morphology and thickness of tungsten silicon nitride crystals were characterized by secondary ion mass spectrometry, scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The results showed that the obtained tungsten silicon nitride crystals were two-dimensional (W5N6)SiN crystals with a hexagonal structure, exhibiting a triangular shape, with an average size of 100 μm and a thickness of about 1.87 nm, and high crystal quality. Example 4

[0038] First, such as Figure 1As shown, in this embodiment, Au foil / W foil (Au foil 5 mm × 5 mm × 10 μm, purity 99.99 wt%, W foil 5 mm × 5 mm × 50 μm, purity 99.95 wt%) and silicon wafer (10 mm × 10 mm × 500 μm, purity 99.9999 wt%) are placed in the central area of ​​a pyrolytic boron nitride tube (inner diameter 16 mm, length 20 cm), with the silicon wafer placed upstream of the Au foil / W foil, 10 mm away from the bimetallic strip. Then, the Au foil / W foil, silicon wafer, and pyrolytic boron nitride tube are placed together in a horizontal reactor (quartz furnace tube). The central region (22 mm in diameter, 20 mm in reaction zone length) is heated to 1070 °C in a hydrogen atmosphere to melt the Au foil (hydrogen flow rate of 200 mL / min and heating rate of 30 °C / min during heating). When the furnace temperature reaches 1070 °C, it is held for 10 minutes, and then a mixture of ammonia and hydrogen is introduced (gas flow rates of 10 mL / min for ammonia and 200 mL / min for hydrogen) to begin the growth of two-dimensional tungsten silicon nitride crystals. The growth time is 300 minutes. After the growth is completed, it is rapidly cooled at a rate of 500 °C / min to obtain a two-dimensional tungsten silicon nitride film on the Au foil surface.

[0039] Then, a polymethyl methacrylate (PMMA) ethyl lactate solution (PMMA accounting for 4 wt%) was dropped onto the Au surface on which two-dimensional tungsten nitride silicon crystals were grown. A PMMA film was then coated using a spin coater at 5000 rpm. After baking at 120°C for 10 minutes, the film was placed in a commercial gold etchant and reacted at 50°C for 120 minutes to dissolve the Au substrate, thus transferring the PMMA / tungsten nitride silicon film onto a SiO2 / Si substrate. Finally, the PMMA was dissolved with acetone at 70°C, thus achieving the successful transfer of the two-dimensional tungsten nitride silicon film.

[0040] The composition, crystal structure, morphology and thickness of tungsten silicon nitride crystals were characterized by secondary ion mass spectrometry, scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The results showed that the obtained tungsten silicon nitride film was a two-dimensional (W5N6)SiN with a hexagonal structure, a thickness of about 1.87 nm and high crystal quality. Example 5

[0041] First, such as Figure 1As shown, in this embodiment, Au foil / W foil (Au foil 5 mm × 5 mm × 10 μm, purity 99.99 wt%, W foil 5 mm × 5 mm × 50 μm, purity 99.95 wt%) and silicon wafer (10 mm × 10 mm × 500 μm, purity 99.9999 wt%) are placed in the central area of ​​a pyrolytic boron nitride tube (inner diameter 16 mm, length 20 cm), with the silicon wafer placed upstream of the Au foil / W foil, 20 mm away from the bimetallic strip. The Au foil / W foil, silicon wafer, and pyrolytic boron nitride tube are then placed together in a horizontal reactor (quartz furnace tube). The central region (22 mm in diameter, 20 mm in reaction zone length) is heated to 1070 °C in a hydrogen atmosphere to melt the Au foil (hydrogen flow rate of 200 mL / min and heating rate of 30 °C / min during heating). When the furnace temperature reaches 1070 °C, it is held for 10 minutes, and then a mixture of ammonia and hydrogen is introduced (gas flow rates of 10 mL / min for ammonia and 200 mL / min for hydrogen) to begin the growth of two-dimensional tungsten silicon nitride crystals. The growth time is 60 minutes. After the growth is completed, it is rapidly cooled at a rate of 500 °C / min to obtain two-dimensional tungsten silicon nitride crystals on the surface of the Au foil.

[0042] Then, a polymethyl methacrylate (PMMA) ethyl lactate solution (PMMA accounting for 4 wt%) was dropped onto the Au surface on which two-dimensional tungsten nitride crystals were grown. A PMMA film was then coated using a spin coater at 5000 rpm. After baking at 120°C for 10 minutes, the film was placed in a commercial gold etchant and reacted at 50°C for 120 minutes to dissolve the Au substrate, transferring the PMMA / tungsten nitride film onto a SiO2 / Si substrate. Finally, the PMMA was dissolved with acetone at 70°C, thus successfully transferring the two-dimensional tungsten nitride crystals.

[0043] The composition, crystal structure, morphology and thickness of tungsten silicon nitride crystals were characterized by secondary ion mass spectrometry, scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The results showed that the obtained tungsten silicon nitride crystals were two-dimensional (W5N6)SiN crystals with a hexagonal structure, exhibiting a triangular shape, with an average size of 10 μm and a thickness of about 1.87 nm, and high crystal quality. Example 6

[0044] First, such as Figure 1As shown, in this embodiment, Au foil / W foil (Au foil 5 mm × 5 mm × 10 μm, purity 99.99 wt%, W foil 5 mm × 5 mm × 50 μm, purity 99.95 wt%) and silicon wafer (10 mm × 10 mm × 500 μm, purity 99.9999 wt%) are placed in the central area of ​​a pyrolytic boron nitride tube (inner diameter 16 mm, length 20 cm), with the silicon wafer placed upstream of the Au foil / W foil, 10 mm away from the bimetallic strip. The Au foil / W foil, silicon wafer, and pyrolytic boron nitride tube are then placed together in a horizontal reaction furnace (quartz furnace). The tube diameter is 22 mm and the reaction zone length is 20 mm. The central area is heated to 1070 °C in a hydrogen atmosphere to melt the Au foil (the hydrogen flow rate is 200 mL / min and the heating rate is 30 °C / min during the heating process). When the furnace temperature reaches 1070 °C, it is held for 10 minutes. Then, a mixture of ammonia and hydrogen is introduced (the gas flow rates are 6 mL / min for ammonia and 200 mL / min for hydrogen) to start the growth of two-dimensional tungsten silicon nitride crystals. The growth time is 60 minutes. After the growth is completed, it is rapidly cooled at a rate of 500 °C / min to obtain two-dimensional tungsten silicon nitride crystals on the surface of the Au foil.

[0045] Then, a polymethyl methacrylate (PMMA) ethyl lactate solution (PMMA accounting for 4 wt%) was dropped onto the Au surface on which two-dimensional tungsten nitride crystals were grown. A PMMA film was then coated using a spin coater at 5000 rpm. After baking at 120°C for 10 minutes, the film was placed in a commercial gold etchant and reacted at 50°C for 120 minutes to dissolve the Au substrate, transferring the PMMA / tungsten nitride film onto a SiO2 / Si substrate. Finally, the PMMA was dissolved with acetone at 70°C, thus successfully transferring the two-dimensional tungsten nitride crystals.

[0046] The composition, crystal structure, morphology and thickness of tungsten silicon nitride crystals were characterized by secondary ion mass spectrometry, scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The results showed that the obtained tungsten silicon nitride crystals were two-dimensional (W3N4)SiN crystals with a hexagonal structure, exhibiting a triangular shape, with an average size of 20 μm and a thickness of about 1.2 nm, and high crystal quality. Example 7

[0047] First, such as Figure 1As shown, in this embodiment, Au foil / W foil (Au foil 5 mm × 5 mm × 10 μm, purity 99.99 wt%, W foil 5 mm × 5 mm × 50 μm, purity 99.95 wt%) and silicon wafer (10 mm × 10 mm × 500 μm, purity 99.9999 wt%) are placed in the central area of ​​a pyrolytic boron nitride tube (inner diameter 16 mm, length 20 cm), with the silicon wafer placed upstream of the Au foil / W foil, 10 mm away from the bimetallic strip. Then, the Au foil / W foil, silicon wafer, and pyrolytic boron nitride tube are placed together in a horizontal reactor (quartz furnace tube). The central region (22 mm in diameter, 20 mm in reaction zone length) is heated to 1070 °C in a hydrogen atmosphere to melt the Au foil (hydrogen flow rate of 200 mL / min and heating rate of 30 °C / min during heating). When the furnace temperature reaches 1070 °C, it is held for 10 minutes, and then a mixture of ammonia and hydrogen is introduced (gas flow rates of 15 mL / min for ammonia and 200 mL / min for hydrogen) to begin the growth of two-dimensional tungsten silicon nitride crystals. The growth time is 60 minutes. After the growth is completed, it is rapidly cooled at a rate of 500 °C / min to obtain two-dimensional tungsten silicon nitride crystals on the surface of the Au foil.

[0048] Then, a polymethyl methacrylate (PMMA) ethyl lactate solution (PMMA accounting for 4 wt%) was dropped onto the Au surface on which two-dimensional tungsten nitride crystals were grown. A PMMA film was then coated using a spin coater at 5000 rpm. After baking at 120°C for 10 minutes, the film was placed in a commercial gold etchant and reacted at 50°C for 120 minutes to dissolve the Au substrate, transferring the PMMA / tungsten nitride film onto a SiO2 / Si substrate. Finally, the PMMA was dissolved with acetone at 70°C, thus successfully transferring the two-dimensional tungsten nitride crystals.

[0049] The composition, crystal structure, morphology and thickness of tungsten silicon nitride crystals were characterized by secondary ion mass spectrometry, scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The results showed that the obtained tungsten silicon nitride crystals were two-dimensional (W7N8)SiN crystals with a hexagonal structure, exhibiting a triangular shape, with an average size of 20 μm and a thickness of about 2.0 nm, and high crystal quality. Example 8

[0050] First, such as Figure 1As shown, in this embodiment, Au foil / W foil (Au foil 5 mm × 5 mm × 10 μm, purity 99.99 wt%, W foil 5 mm × 5 mm × 50 μm, purity 99.95 wt%) and a quartz plate (10 mm × 10 mm × 500 μm, purity 99.9999 wt%) are placed in the central area of ​​a pyrolytic boron nitride tube (inner diameter 16 mm, length 20 cm), with the quartz plate placed upstream of the Au foil / W foil, 10 mm away from the bimetallic strip. Then, the Au foil / W foil, the quartz plate, and the pyrolytic boron nitride tube are placed together in a horizontal reactor (quartz...). The furnace tube has a diameter of 22 mm and a reaction zone length of 20 mm. The central area is heated to 1070 °C in a hydrogen atmosphere to melt the Au foil (the hydrogen flow rate during heating is 200 mL / min, and the heating rate is 30 °C / min). When the furnace temperature reaches 1070 °C, it is held for 10 minutes. Then, a mixture of ammonia and hydrogen is introduced (the gas flow rates are 10 mL / min for ammonia and 200 mL / min for hydrogen) to begin the growth of two-dimensional tungsten silicon nitride crystals. The growth time is 60 minutes. After the growth is completed, the furnace is rapidly cooled at a rate of 500 °C / min to obtain two-dimensional tungsten silicon nitride crystals on the surface of the Au foil.

[0051] Then, a polymethyl methacrylate (PMMA) ethyl lactate solution (PMMA accounting for 4 wt%) was dropped onto the Au surface on which two-dimensional tungsten nitride crystals were grown. A PMMA film was then coated using a spin coater at 5000 rpm. After baking at 120°C for 10 minutes, the film was placed in a commercial gold etchant and reacted at 50°C for 120 minutes to dissolve the Au substrate, transferring the PMMA / tungsten nitride film onto a SiO2 / Si substrate. Finally, the PMMA was dissolved with acetone at 70°C, thus successfully transferring the two-dimensional tungsten nitride crystals.

[0052] The composition, crystal structure, morphology and thickness of tungsten silicon nitride crystals were characterized by secondary ion mass spectrometry, scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The results showed that the obtained tungsten silicon nitride crystals were two-dimensional (W5N6)SiN crystals with a hexagonal structure, exhibiting a triangular shape, with an average size of 20 μm and a thickness of about 1.87 nm, and high crystal quality. Example 9

[0053] First, such as Figure 1As shown, in this embodiment, Au foil / W foil (Au foil 5 mm × 5 mm × 10 μm, purity 99.99 wt%, W foil 5 mm × 5 mm × 50 μm, purity 99.95 wt%) and silicon wafer (10 mm × 10 mm × 500 μm, purity 99.9999 wt%) are placed in the central area of ​​a pyrolytic boron nitride tube (inner diameter 16 mm, length 20 cm). A mixture of 1 g of silicon powder and alumina powder (mass ratio of silicon powder to alumina powder 1:50) is placed upstream of the Au foil / W foil, with the mixture 10 mm away from the bimetallic sheet. Then, the Au foil / W foil and the mixture of silicon powder and alumina powder are... The material and the pyrolytic boron nitride tube were placed together in the central area of ​​a horizontal reactor (quartz furnace tube diameter 22 mm, reaction zone length 20 mm); the Au foil was heated to 1070℃ in a hydrogen atmosphere to melt it (hydrogen flow rate was 200 mL / min, heating rate was 30℃ / min). When the furnace temperature reached 1070℃, it was held for 10 minutes, and then a mixture of ammonia and hydrogen was introduced (gas flow rates were 10 mL / min for ammonia and 200 mL / min for hydrogen) to begin the growth of two-dimensional silicon tungsten nitride crystals. The growth time was 60 minutes. After the growth was completed, it was rapidly cooled at a rate of 500℃ / min to obtain two-dimensional silicon tungsten nitride crystals on the surface of the Au foil.

[0054] Then, a polymethyl methacrylate (PMMA) ethyl lactate solution (PMMA accounting for 4 wt%) was dropped onto the Au surface on which two-dimensional tungsten nitride crystals were grown. A PMMA film was then coated using a spin coater at 5000 rpm. After baking at 120°C for 10 minutes, the film was placed in a commercial gold etchant and reacted at 50°C for 120 minutes to dissolve the Au substrate, transferring the PMMA / tungsten nitride film onto a SiO2 / Si substrate. Finally, the PMMA was dissolved with acetone at 70°C, thus successfully transferring the two-dimensional tungsten nitride crystals.

[0055] The composition, crystal structure, morphology and thickness of tungsten silicon nitride crystals were characterized by secondary ion mass spectrometry, scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The results showed that the obtained tungsten silicon nitride crystals were two-dimensional (W5N6)SiN crystals with a hexagonal structure, exhibiting a triangular shape, with an average size of 20 μm and a thickness of about 1.87 nm, and high crystal quality. Example 10

[0056] First, such as Figure 1As shown, in this embodiment, Au foil / W foil (Au foil 5 mm × 5 mm × 10 μm, purity 99.99 wt%, W foil 5 mm × 5 mm × 50 μm, purity 99.95 wt%) and silicon wafer (10 mm × 10 mm × 500 μm, purity 99.9999 wt%) are placed in the central area of ​​a pyrolytic boron nitride tube (inner diameter 16 mm, length 20 cm). A mixture of 1 g of quartz powder and alumina powder (mass ratio of quartz powder to alumina powder 1:50) is placed upstream of the Au foil / W foil, with the mixture 10 mm away from the bimetallic strip. Then, the Au foil / W foil, quartz powder, and alumina powder... The mixture and the pyrolytic boron nitride tube were placed together in the central area of ​​a horizontal reactor (quartz furnace tube diameter 22 mm, reaction zone length 20 mm); the Au foil was melted by heating to 1070 °C in a hydrogen atmosphere (hydrogen flow rate 200 mL / min, heating rate 30 °C / min). When the furnace temperature reached 1070 °C, it was held for 10 minutes, and then a mixture of ammonia and hydrogen was introduced (gas flow rates of ammonia 10 mL / min and hydrogen 200 mL / min, respectively) to start the growth of two-dimensional silicon tungsten nitride crystals. The growth time was 60 minutes. After the growth was completed, it was rapidly cooled at a rate of 500 °C / min to obtain two-dimensional silicon tungsten nitride crystals on the surface of the Au foil.

[0057] Then, a polymethyl methacrylate (PMMA) ethyl lactate solution (PMMA accounting for 4 wt%) was dropped onto the Au surface on which two-dimensional tungsten nitride crystals were grown. A PMMA film was then coated using a spin coater at 5000 rpm. After baking at 120°C for 10 minutes, the film was placed in a commercial gold etchant and reacted at 50°C for 120 minutes to dissolve the Au substrate, transferring the PMMA / tungsten nitride film onto a SiO2 / Si substrate. Finally, the PMMA was dissolved with acetone at 70°C, thus successfully transferring the two-dimensional tungsten nitride crystals.

[0058] The composition, crystal structure, morphology and thickness of tungsten silicon nitride crystals were characterized by secondary ion mass spectrometry, scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The results showed that the obtained tungsten silicon nitride crystals were two-dimensional (W5N6)SiN crystals with a hexagonal structure, exhibiting a triangular shape, with an average size of 20 μm and a thickness of about 1.87 nm, and high crystal quality. Example 11

[0059] First, such as Figure 1As shown, in this embodiment, Au foil / Mo foil (Au foil 5 mm × 5 mm × 10 μm, purity 99.99 wt%, Mo foil 5 mm × 5 mm × 50 μm, purity 99.95 wt%) and silicon wafer (10 mm × 10 mm × 500 μm, purity 99.9999 wt%) are placed in the central area of ​​a pyrolytic boron nitride tube (inner diameter 16 mm, length 20 cm), with the silicon wafer placed upstream of the Au foil / Mo foil, 10 mm away from the bimetallic strip. Then, the Au foil / Mo foil, silicon wafer, and pyrolytic boron nitride tube are placed together in a horizontal reactor (quartz). The furnace tube has a diameter of 22 mm and a reaction zone length of 20 mm. The central area is heated to 1070 °C in a hydrogen atmosphere to melt the Au foil (the hydrogen flow rate during heating is 200 mL / min, and the heating rate is 30 °C / min). When the furnace temperature reaches 1070 °C, it is held for 10 minutes. Then, a mixture of ammonia and hydrogen is introduced (the gas flow rates are 10 mL / min for ammonia and 200 mL / min for hydrogen) to begin the growth of two-dimensional molybdenum silicon nitride crystals. The growth time is 60 minutes. After the growth is completed, the furnace is rapidly cooled at a rate of 500 °C / min to obtain two-dimensional molybdenum silicon nitride crystals on the surface of the Au foil.

[0060] Then, a polymethyl methacrylate (PMMA) ethyl lactate solution (PMMA accounting for 4 wt%) was dropped onto the Au surface on which two-dimensional molybdenum silicon nitride crystals were grown. A PMMA film was then coated using a spin coater at 3000 rpm. After baking at 120°C for 10 minutes, the film was placed in a commercial gold etchant and reacted at 50°C for 120 minutes to dissolve the Au substrate, transferring the PMMA / molybdenum silicon nitride crystals onto the SiO2 / Si substrate. Finally, the PMMA was dissolved with acetone at 70°C, thus achieving the successful transfer of the two-dimensional molybdenum silicon nitride crystals.

[0061] The composition, crystal structure, morphology and thickness of the molybdenum silicon nitride crystal were characterized by secondary ion mass spectrometry, scanning electron microscopy, transmission electron microscopy and atomic force microscopy. The results showed that the obtained molybdenum silicon nitride crystal was a two-dimensional (Mo5N6)SiN crystal with a hexagonal structure, exhibiting a triangular shape, with an average size of 20 μm and a thickness of about 1.7 nm, and high crystal quality.

[0062] like Figure 2 As shown, scanning electron microscope images of two-dimensional (W5N6)SiN ternary compounds obtained at different growth times on Au / W substrates show that as the growth time increases, the (W5N6)SiN samples gradually evolve from small-sized independent single crystals to large-sized continuous films.

[0063] like Figure 3 As shown, the atomic force microscopy image shows that the thickness of (W5N6)SiN is 1.87 nm.

[0064] like Figure 4 As shown, the secondary ion mass spectrometry surface scan image of the Au / W substrate with (W5N6)SiN growth reveals that the sample contains three elements: W, Si, and N.

[0065] like Figure 5 As shown, the planar high-resolution scanning transmission electron microscopy (STEM) image and the cross-sectional high-resolution integrated differential phase STEM image indicate that (W5N6)SiN has a single-sided passivated structure, and its atomic arrangement in the vertical direction is NWNWNWNWNWN-Si-N.

[0066] like Figure 6 As shown, the micro-area absorption spectrum and photoluminescence spectrum indicate that (W5N6)SiN has semiconductor properties with a band gap of approximately 2.4 eV.

[0067] like Figure 7 As shown in the scanning electron microscope images, the two-dimensional (Mo5N6)SiN ternary compound grown on the Au / Mo substrate has a regular morphology.

[0068] like Figure 8 As shown in the image, the secondary ion mass spectrometry surface scan image reveals that the sample contains three elements: Mo, Si, and N.

Claims

1. A novel class of two-dimensional ternary compounds with a single-sided passivation structure, characterized in that, The molecular formula of this type of ternary compound is (M n Z n+1 )AZ, where: M is a metallic element, A is a Group 4 element, Z is a Group 5 element, and n is a positive integer; this compound can be viewed as an AZ bilayer paired with a two-dimensional M n Z n+1 Obtained by passivation of one side of the compound.

2. A method for preparing a novel two-dimensional ternary compound with a single-sided passivation structure as described in claim 1, characterized in that, A bimetallic layer consisting of an upper Au layer and a lower metal M layer was used as the growth substrate. Au served as a diffusion channel for the metal M, providing the M element. A and Z elements were introduced under a carrier gas atmosphere. By reducing the supply of A element, an A-depleted environment was created. Large-sized, controllable-thickness (M) deposits were grown on the Au surface via chemical vapor deposition at a reaction temperature above the melting point of Au. n Z n+1 )AZ crystal domains and their thin films, followed by etching away Au (M n Z n+1 )AZ is transferred to any matrix.

3. A method for preparing a novel two-dimensional ternary compound with a single-sided passivation structure according to claim 2, characterized in that, The bimetallic layer growth substrate uses stacked Au foil and metal M foil; or the M element can be obtained by magnetron sputtering or thermal evaporation on a partially high melting point metal foil.

4. A method for preparing a novel two-dimensional ternary compound with a single-sided passivation structure according to claim 2, characterized in that, A and Z elements are introduced by using precursors containing A and Z. The precursors are solids, powders, liquids or gases that volatilize or decompose to release A or Z at high temperatures.

5. A method for preparing a novel two-dimensional ternary compound with a single-sided passivation structure according to claim 4, characterized in that, M represents a metallic element, including molybdenum, tungsten, titanium, zirconium, hafnium, vanadium, niobium, tantalum, or chromium; A represents a Group IV element, including silicon or germanium. Precursors for silicon include silicon wafers, quartz wafers, silanes, silicon powder, mixtures of silicon powder and alumina powder, quartz powder, and mixtures of quartz powder and alumina powder; precursors for germanium include germanium wafers, germanane, germanium powder, mixtures of germanium powder and alumina powder, germanium oxide powder, and mixtures of germanium oxide powder and alumina powder; Z represents a Group V element, including nitrogen, phosphorus, or arsenic. Precursors for nitrogen include ammonia, precursors for phosphorus include white phosphorus or red phosphorus, and precursors for arsenic include elemental arsenic.

6. A method for preparing a novel two-dimensional ternary compound with a single-sided passivation structure according to claim 2, characterized in that, In the chemical vapor deposition (CVD) reaction, the carrier gas is hydrogen or a mixture of hydrogen and an inert gas; CVD grows two-dimensional layered structures (M... n Z n+1 The temperature range for the AZ two-dimensional ternary compound is 1070℃~1200℃, and the growth time is 30 minutes~300 minutes. By extending the growth time, the (M) can be increased. n Z n+1 The size of the AZ domains is determined to obtain a complete continuous thin film.

7. A method for preparing a novel two-dimensional ternary compound with a single-sided passivation structure according to claim 2, characterized in that, New type (M) n Z n+1 The single-sided passivation structure of AZ two-dimensional ternary compounds can be achieved by reducing the supply of element A to create an A-depleted environment, including: increasing the distance between the A element precursor and the growth substrate, reducing the amount of A element precursor, reducing the growth temperature, or any combination of two or three operations.

8. A method for preparing a novel two-dimensional ternary compound with a single-sided passivation structure according to claim 2, characterized in that, New type (M) n Z n+1 The thickness of AZ two-dimensional ternary compounds can be controlled by altering the amount of Z element precursor, growth temperature, and growth time during chemical vapor deposition: extending the growth time or increasing the amount of Z element precursor can yield thicker (M) ternary compounds. n Z n+1 )AZ two-dimensional ternary compound.

9. A method for preparing a novel two-dimensional ternary compound with a single-sided passivation structure according to claim 2, characterized in that, In the transfer (M n Z n+1 When processing AZ two-dimensional ternary compounds, a layer of polymer is first uniformly coated on its surface to prevent damage during subsequent processing. Then, the Au substrate is removed by etching with an Au etching solution to obtain the polymer / (M n Z n+1 The AZ two-dimensional ternary compound was used, and finally the composite film was placed on the target substrate. The polymer protective film was dissolved and removed using an organic solvent.

10. A method for preparing a novel two-dimensional ternary compound with a single-sided passivation structure according to claim 9, characterized in that, The polymer used is one or a mixture of two or more of polymethyl methacrylate, polyethylene, polystyrene, and polypropylene. The etching solution for Au is a commercial gold etchant. The organic solvent used to remove the polymer protective layer is one or a mixture of two or more of ketones, chlorinated hydrocarbons, halogenated hydrocarbons, and aromatic hydrocarbons.